Globalisation, development, and culture : Essays in honour of Professor S.P. Nagendra - Lakshmanna, C. ; Sahai Jugendra (Jaipur, INDIA: Rawat Publications, 2012)
S.P. Nagendra, Indian social scientist; contributed articles